Resposta :
Explicação passo-a-passo:
a)
[tex] \frac{1}{2} + \frac{5}{6} = \frac{(3 \times 1) + 5}{6} = \frac{3 + 5}{6} = \frac{8}{6} = \frac{4}{3} [/tex]
b)
[tex] \frac{3}{4} - \frac{1}{2} = \frac{3 - (2 \times 1)}{4} = \frac{3 - 2}{4} = \frac{1}{4} [/tex]
c)
[tex] \frac{5}{6} - \frac{1}{3} = \frac{5 - (2 \times 1)}{6} = \frac{5 - 2}{6} = \frac{3}{6} = \frac{1}{2} [/tex]
d)
[tex] \frac{1}{3} + \frac{5}{6} = \frac{(2 \times 1) + 5}{6} = \frac{2 + 5}{6} = \frac{7}{6} [/tex]
e)
[tex] \frac{2}{5} - \frac{3}{10} = \frac{(2 \times 2) - 3}{10} = \frac{4 - 3}{10} = \frac{1}{10} [/tex]
f)
[tex] \frac{1}{3} - \frac{1}{6} = \frac{(2 \times 1) - 1}{6} = \frac{2 - 1}{6} = \frac{1}{6} [/tex]